The synthesis and alkylation of p-tetrakischloro-calix[4]arene - E. A. Ivanova; T. V. Glukhareva; Yu. Yu. Morzherin (Chimica Techno Acta)
This work is devoted to the development of a chlorination of a calixarenes and a testing of the methods for their preparation to investigate the biological activity of the obtained compounds. New convinient undescribed in the literature methods of the chlorination using sulphuryl chloride or sodium hypochlorite were designed. By the using de-tert-butylcalix[4]arene, containing lower rin the ethoxy(hydroxy)carbonyl metoxy groups, as the starting compounds in the same reactin l aed to mixture of the produts. The reaction of the calix[4]arene and the sulfuryl chloride led to the tetra-kis-chlorocalix[4]arene with good yield (95 %).